Respuesta :
Answer:
x = -1
y = 1
Step-by-step explanation:
We need to use simultaneous equations to answer this question. Since x is already by itself in one of the equations, we'll use substitution.
When rearranging the second equation, in terms of x:
x + 2y = 1
x = 1 - 2y (subtract both sides by 2y)
Now we can substitute this into the first equation and we'll only have one variable:
3(1 - 2y) - 1/2y = -7/2
3 - 6y - 1/2 y = -7/2
3 - 6 1/2y = -7/2
3 + 7/2 = 6 1/2 y
6 1/2 = 6 1/2 y
y = 1
Now that we know y, we can find x by substituting the y value into any of the given equations.
x + 2y = 1
x + 2(1) = 1
x + 2 = 1
x = 1 - 2
x = -1
Hope this helps,
Cate